2022
DOI: 10.3390/pr10122675
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation from Organic Wastes: A New Generation of Bioproducts

Abstract: Solid-state fermentation (SSF) is part of the pathway to consolidate waste as a relevant alternative for the valorization of organic waste. The objective of SSF is to produce one or several bioproducts of added value from solid substrates. Solid-state fermentation can use a wide variety of organic waste as substrates thus, it is an excellent candidate in the framework of the circular bioeconomy to change the status of waste from feedstock. The development of SSF was boosted in the previous decade by scientific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…However, compared with the results obtained by Rodríguez et al (2020), who reported a crude SL yield of 0.2 g g -1 DM i using WOC and molasses as feedstock at 22 and 100 L, respectively, the SL yields achieved in this study are lower. Nevertheless, it should be considered that the present experiment was set up at a flask scale, and in this sense, the results could be improved in a scale-up process applying aeration and agitation (Raghavarao et al, 2003;Oiza et al, 2022).…”
Section: Alternative Substrates For Sl Production In Ssfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, compared with the results obtained by Rodríguez et al (2020), who reported a crude SL yield of 0.2 g g -1 DM i using WOC and molasses as feedstock at 22 and 100 L, respectively, the SL yields achieved in this study are lower. Nevertheless, it should be considered that the present experiment was set up at a flask scale, and in this sense, the results could be improved in a scale-up process applying aeration and agitation (Raghavarao et al, 2003;Oiza et al, 2022).…”
Section: Alternative Substrates For Sl Production In Ssfmentioning
confidence: 99%
“…SSF is developed in the absence or limitation of free water (Pandey, 2003) and allows the sustainable conversion of organic insoluble solid waste into high-value-added products (Jiménez-Peñalver et al, 2016;Hu et al, 2021). The main challenges of SSF revolve around sample heterogenicity and mass and heat transfer, which are intrinsic characteristics of solid matrices (Kumar et al, 2021;Oiza et al, 2022). Temperature and composition gradients are often reported when scaling up SSF systems, pointing to the co-existence of different metabolic states for cells growing in the solid matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SSF can be a way of recycling such wastes, as they are a source of pollution that must be disposed of. Another factor that could reduce costs is the fact that it does not require to use energy to heat the process [ 66 , 214 , 215 , 216 ]. As with other techniques, SSF has limitations.…”
Section: Ssf For Sustainable Agriculture: Advantages and Limitationsmentioning
confidence: 99%
“…This allows SSF to be a more cost-effective and lower solvents usage process than SmSF. The SSF constraints, the numerous approaches being used to solve them, and the potential future directions for further developing this biotechnology to increase its competitiveness in the worldwide market were all covered in detail by Oiza et al [ 216 ].…”
Section: Ssf For Sustainable Agriculture: Advantages and Limitationsmentioning
confidence: 99%
“…In practical terms, SSF takes place in a bioreactor, typically aerobic, which is filled with the solid substrate and inoculated with the strain of interest to produce the desired bioproduct [6]. Once produced, this bioproduct must be recovered, although in some cases the final fermented solid can be used as end product, without a defined downstream process [7].…”
Section: Introductionmentioning
confidence: 99%